Inherited competence and spin-off performance. Issue 3 (3rd March 2016) - Curran, Declan; van Egeraat, Chris; O'Gorman, Colm
ABSTRACT: In this paper we extend the hereditary theory of spin-off formation, developed by Klepper, by relating the concept of inherited competence to two different types of spin-offs—university and private sector spin-offs—and two different types of inherited competence—R&D competence and innovation competence. We then utilize this extension of Klepper's framework to study the evolution of a science-based industry—the biotech industry. Using the Irish biotech industry as a case-study, we find that differences in pre-entry experience manifest themselves most markedly in terms of the firm's capacity to attract venture capital, with private sector spin-offs considerably outperforming university spin-offs. We argue that the superior performance of the private sector spin-offs is explained by the nature of their inherited competence in that they are characterized by higher levels of innovation competence.